Sistem Informasi Akuntansi Prosedur Penagihan Piutang Pelanggan Indihome dan Indibiz pada Pt Telkom Witel Karawang - Yeffi Dwi agusthin; Dhea Imroatul Fatihah (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This research is motivated by the problem of customer receivables that are delayed in payment, so that an accounting information system is needed as a means of control to ensure that the collection procedure runs effectively and efficiently. Using a qualitative descriptive method with observation, interviews, and documentation. The results of the study indicate that the Indihome and Indibiz collection procedures by the Billing and Payment Collection unit are in accordance with the company's SOP.